Pemberian Makanan Bergizi Berupa Olahan Daging Sapi kepada Anak-Anak Dusun Toinaman Pulau Moa - Asmirani Alam; Ratnah Kurniati MA; Sitti Fatimah Kamaruddin; Lestari Lestari; Edy Sony; Sigit Sugiarto; Dian Rubiana Suherman; Juwaher Makatita; Arnold I. Kewilaa; Inggrid Welerubun; Jecklin M. Lainsamputty; Micael Ririhena (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Toinaman Hamlet is located on Moa Island, the condition of the hamlet is remote, limited infrastructure, minimal access to basic services and is an isolated hamlet.  Most of the residents in this hamlet are very dependent on the weather and natural products to survive. When natural conditions are unfavorable, such as storms, drought or rough seas, their source of livelihood is significantly disrupted. This of course greatly affects the ability of local hamlet communities to be able to meet their nutritional food needs, especially to fulfill their children's nutrition. Fulfilling nutrition for children in rural areas often faces its own challenges, especially related to access to a variety of nutritious foods. Some common problems include limited food ingredients, traditional diets that may lack diversity, and limited knowledge about nutrition. One source of nutritious food that is important for health is beef.  Beef is a good source of protein for children because it contains many important nutrients such as iron, zinc and vitamin B12, all of which support their growth and development. The PKM activity carried out is in the form of providing nutritious food in the form of processed beef to the children of Toinaman Hamlet, Moa Island. The aim is to improve the nutrition of the hamlet children, prevent malnutrition and nutritional deficiencies and support the growth and development of the children of Toinaman Hamlet, Moa Island. The food products provided are food products made from beef, namely rendang products